Pay What You Want as a Marketing Strategy in Monopolistic and Competitive Markets - Klaus M. Schmidt; Martin Spann; Robert Zeithammer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
Pay What You Want (PWYW) can be an attractive marketing strategy to price discriminate between fair-minded and selfish customers, to fully penetrate a market without giving away the product for free, and to undercut competitors that use posted prices. We report on laboratory experiments that identify causal factors determining the willingness of buyers to pay voluntarily under PWYW. Furthermore, to see how competition affects the viability of PWYW, we implement markets in which a PWYW seller competes with a traditional seller. Finally, we endogenize the market structure and let sellers choose their pricing strategy. The experimental results show that outcome-based social preferences and strategic considerations to keep the seller in the market can explain why and how much buyers pay voluntarily to a PWYW seller. We find that PWYW can be viable in isolation, but it is less successful as a competitive strategy because it does not drive traditional posted-price sellers out of the market. Instead, the existence of a posted-price competitor reduces buyers' payments and prevents the PWYW seller from fully penetrating the market. If given the choice, the majority of sellers opt for setting a posted price rather than a PWYW pricing. We discuss the implications of these results for the use of PWYW as a marketing strategy.
urn:nbn:de:bvb:19-epub-14312-8
Keywords: 330; customer-driven pricing mechanisms; pay what you want; revenue management; price discrimination; social preferences